Development of Adobe Flash Learning Media Based on Metacognitive Ability as a Learning Innovation during the Covid-19 Pandemic - Nurhayati, Ina; Aripin, Aripin; Ni'mah, Khomsatun (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to develop adobe flash learning media based on metacognitive abilities. The research method used is research and development (R&D) with the ADDIE model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation.This research was conducted at SMA Negeri 1 Bantarkalong in the odd semester of the 2021/2022 academic year. Limited trials were carried out on five students of class XII MIPA 1, and field tests were carried out on class XII MIPA 2, which amounted to 21 people. The validation results of material and media experts stated that the adobe flash learning media based on metacognitive abilities was valid and could be used with some improvements.Based on the questionnaire responses, the limited trial students scored 191 in the "Good" category.At the same time, the results of the teacher's response questionnaire got a score of 132 in the "Very Good" class.Then the teaching activity observation sheet results obtained a teaching implementation score of 94% with the "Very Good" category. In addition, the results of the questionnaire responses from field test students scored 866 in the "Very Good" category.